2021
DOI: 10.1002/asia.202100044
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Matrices for the Analysis of Low Molecular Weight Compounds: Rational Design, Challenges and Perspectives

Abstract: The analysis of low molecular weight (LMW) compounds is of great interest to detect small pharmaceutical drugs rapidly and sensitively, or to trace and understand metabolic pathways. Matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) plays a central role in the analysis of high molecular weight (bio)molecules. However, its application for LMW compounds is restricted by spectral interferences in the low m/z region, which are produced by conventional organic matrices. Several strategies reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 121 publications
(216 reference statements)
0
24
0
Order By: Relevance
“…It is possible to monitor the reaction by ESI or MALDI mass spectrometry using the negative mode detection. Two reviews reported the best matrix and conditions to use when running MALDI/ TOF 279 or ESI 280 mass spectra for small molecules or corrole derivatives. Very interestingly, the UV-visible spectra of the isolated tetra-thiocyanatocorroles show, in acetonitrile, the presence of four Q-bands, quite similar to the Q-type bands of chlorophyll-a.…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%
“…It is possible to monitor the reaction by ESI or MALDI mass spectrometry using the negative mode detection. Two reviews reported the best matrix and conditions to use when running MALDI/ TOF 279 or ESI 280 mass spectra for small molecules or corrole derivatives. Very interestingly, the UV-visible spectra of the isolated tetra-thiocyanatocorroles show, in acetonitrile, the presence of four Q-bands, quite similar to the Q-type bands of chlorophyll-a.…”
Section: Photodynamic Therapy (Pdt) Applicationsmentioning
confidence: 99%
“…The selection of a suitable matrix, together with the deposition method of the matrix, contributes to the detection sensitivity, spatial resolution and mass range of MSI results [ 113 , 114 ]. Numerous secondary metabolites in TCM plants fall into the category of low molecular weight compounds, the MS signals of which could be interfered by the background signals from classic small organic matrices such as 2,5-dihydroxybenzoic acid (DHB), α -cyano-4-hydroxycinnamic acid (CHCA), and 9-aminoacridine (9-AA) [ 115 ]. These classic matrices have been commonly applied in TCM analysis, as can be seen in Table 1 .…”
Section: Main Textmentioning
confidence: 99%
“…Despite all its advantages (high sensitivity, rapidness and efficiency), the MALDI method is rarely used for detection and quantification of low molecular weight (LMW) compounds. The main problem is the need for application of matrices, which are usually low molecular weight acids and during analysis produce variety of ions which may interfere with signals of analyzed sample in low mass range 6 . This problem can be solved with application of nanoparticles instead of traditional organic matrices; many articles have been published showing the use of nanoparticles in LMW analysis 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…The main problem is the need for application of matrices, which are usually low molecular weight acids and during analysis produce variety of ions which may interfere with signals of analyzed sample in low mass range. 6 This problem can be solved with application of nanoparticles instead of traditional organic matrices; many articles have been published showing the use of nanoparticles in LMW analysis. [7][8][9][10] Monoisotopic silver-109 nanoparticles ( 109 AgNPs) were found to be very efficient for cationization of various type of compounds, for example, amino acids, fatty acids, saccharides, or mould toxins.…”
Section: Introductionmentioning
confidence: 99%